2017
DOI: 10.1007/s00384-017-2792-x
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of the superior rectal artery: influence of surgical technique on anastomotic healing and postoperative morbidity in laparoscopic sigmoidectomy for diverticular disease

Abstract: Preservation of the SRA seems to be associated with favorable outcome in patients undergoing laparoscopic sigmoid resection for diverticular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 15 publications
0
31
0
1
Order By: Relevance
“…The methodological evaluation of the non‐RCTs with the MINORS scale showed that two studies scored 21 points (high quality) , two had 17 points and the other two studies scored 10 points (poor quality) (Appendix ). In the non‐RCTs there was a possible selection bias associated with the decision to preserve or to ligate the IMA.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The methodological evaluation of the non‐RCTs with the MINORS scale showed that two studies scored 21 points (high quality) , two had 17 points and the other two studies scored 10 points (poor quality) (Appendix ). In the non‐RCTs there was a possible selection bias associated with the decision to preserve or to ligate the IMA.…”
Section: Resultsmentioning
confidence: 99%
“…The electronic search strategy identified 145 citations. After the initial screening of the titles and abstracts and removal of duplications, 58 titles remained, of which 15 were considered relevant [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. A total of eight studies met the inclusion criteria and were included in the analysis [16][17][18][19][20][21][22][23] and seven studies were excluded [24][25][26][27][28][29][30] (see Appendix S1 in the online Supporting Information).…”
Section: Results Of the Searchmentioning
confidence: 99%
See 2 more Smart Citations
“…Sohn et al [12] Explicit definition: (1) clinically as manifestation with fever, septicemia and abdominal pain/peritonitis and/or extravasation of bowel content and/or gas through drainage or wound, confirmed by radiographic analysis or digital rectal examination or endoscopy, (2) evidence of local peritonitis and/or leakage of bowel content and/or gas from the anastomosis into the abdomen or pelvis within reoperation. Radiologic signs of anastomotic leakage were surrounding gas and/or fluid collection as well as extraluminal detection of contrast agent after enema.…”
Section: Author Definition Anastomotic Leakmentioning
confidence: 99%